2012
DOI: 10.1039/c2dt30119a
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the alkene size and the nature of the metal ion in metal–alkene complexes: a theoretical study

Abstract: Cation interactions with π-systems are a problem of outstanding contemporary interest and the nature of these interactions seems to be quite different for transition and main group metal ions. In this paper, we have systematically analyzed the contrast in the bonding of Cu(+) and main group metal ions. The molecular structures and energetics of the complexes formed by various alkenes (A = C(n)H(2n), n = 2-6; C(n)H(2n- 2), n = 3-8 and C(n)H(2n + 2), n = 5-10) and metal ions (M = Li(+), Na(+), K(+), Ca(2+), Mg(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…Further, frequency calculations at B3LYP/6-31G(d) level of theory characterized all monomers as minima on the PES. From the literature, it is well known that the M05-2X functional is suitable for treating non-covalent interactions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In our previous studies of phenylalanine, tyrosine and tryptophan monomers, we have also found the M05-2X functional to give satisfactory results [17][18][19].…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Further, frequency calculations at B3LYP/6-31G(d) level of theory characterized all monomers as minima on the PES. From the literature, it is well known that the M05-2X functional is suitable for treating non-covalent interactions [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In our previous studies of phenylalanine, tyrosine and tryptophan monomers, we have also found the M05-2X functional to give satisfactory results [17][18][19].…”
Section: Methodsmentioning
confidence: 72%
“…Chakrabarti et al [20] reported that the His ring interacts with other aromatic and basic residues and forms hydrogen bonds (HBs) with polar and charged (both negative and positive) residues in proteins. Recent studies on the cooperativity of non-covalent interactions reveal that the manifestation of cooperativity is essential to understand various phenomena such as formation of supramolecular assemblies, catalysis and biological functions [1,[21][22][23][24]. His is an important model for the understanding of cation-π interactions due to its imidazole side chain [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The modulation in the strength of cation−π interactions due to the size of the π-system and the nature of the cation have already been demonstrated by our group. 22,24 The present study shows that the larger the alkane size, the stronger the cation−alkane interaction, and thus provides an explanation for the decrease of cation mobility in liquid alkanes as the alkane size increases. 74 The BE of Li + -A10 (34.51 kcal/mol) is competitive with the BE of Li + -H 2 O (experimental value = 34.02 kcal/mol 75 and computed value = 32.69 kcal/mol 95 ).…”
Section: Resultsmentioning
confidence: 83%
“…This choice is supported by numerous previous studies that have employed MP2 optimized or reoptimized structures as a reference for transition metal complexes, especially for (but not limited to) closed-shell, singlet species [24-33]. The computed structures of the literature compounds were compared directly to the experimentally determined crystal structures from the cif file from the CCDC [12].…”
Section: Methodsmentioning
confidence: 99%